Comparing a daily versus weekly titration algorithm in people with type 2 diabetes switching from basal insulin to iGlarLixi in the LixiLan ONE CAN randomized trial. Issue 10 (29th June 2022) - Hramiak, Irene; Gerstein, Hertzel C.; Leiter, Lawrence A.; Yale, Jean‐François; Bajaj, Harpreet S.; Stewart, John; Toutounji, Marie‐Josée; Harris, Stewart B.
Abstract: Aim: To compare the efficacy and safety of a simple daily titration algorithm compared with a weekly dose adjustment of iGlarLixi in people with type 2 diabetes. Materials and Methods: LixiLan ONE CAN (NCT03767543), a randomized, 26‐week, open‐label, multicentre phase 3 trial conducted in Canada, involved 265 people with type 2 diabetes and an HbA1c of ≥7.5% to ≤ 10.5% or less (≥58 to ≤91 mmol/mol) on basal insulin for 6 months or longer. Participants were randomized 1:1 with instructions to self‐titrate iGlarLixi daily (1 unit/day) or once weekly (2 or 4 units/week) to a common target fasting plasma glucose of 4.4 to 5.6 mmol/L (79 to 101 mg/dl). The primary objective was to show non‐inferiority of the daily versus weekly titration algorithm. Results: At 26 weeks, daily titration of iGlarLixi was not inferior to a weekly titration for both the prespecified primary endpoint of change in HbA1c from baseline (least square [LS] mean change: −1.24% vs. −0.92%, respectively; LS mean difference: 0.32%; 95% CI [0.07, 0.57]; P < .0001) and for the secondary endpoint of change in weight from baseline (LS mean change: −0.22 vs. +0.81 kg, respectively; LS mean difference: 1.03 kg; 95% CI [0.01, 2.06]; P < .0001). Indeed, for both the primary and secondary outcome, the daily titration of iGlarLixi was superior. There were no statistically significant differences in hypoglycaemia incidence between the two titration strategies during the 26‐week study. Conclusion: A daily titration algorithm for switching basal insulin to iGlarLixi was shown to be non‐inferior and superior for glycaemic control and weight compared with weekly titration.